Foraminiferal isotope record across the latest Albian Oceanic Anoxic Event 1d at ODP Sites 1050 and 1052 (Blake Nose, western north Atlantic) - Maria Rose Petrizzo; Brian T. Huber; Paul A. Wilson (Val-impressions, 2005)
A detailed and high resolution investigation of organic carbon-rich sediments of latest Albian age is presented. This record was recovered on Blake Nose at Ocean Drilling Program (ODP) Sites 1050 and 1052, located in the western North Atlantic (paleolatitude 30°N). The rhythmically bedded, organic-rich black shale found at those sites corresponds to Oceanic Anoxic Event (OAE) 1d, falls in the upper part of the planktonic foraminiferal Rotalipora appenninica Zone, and is comprised within the stratigraphic interval identified by the total range of the distinctive biomarker Planomalina buxtorfi. This event is widely preserved as a black shale across eastern and western Tethys of latest Albian age (~98.9-100.1 Ma) with sporadic occurrences also in the South Atlantic, southern Indian, and Eastern Pacific ocean basins. Despite such widespread distribution of this latest Albian event, Sites 1050 (2296 m water depth) and 1052 (1345 m water depth) are the only sites in the world where a detailed time slice study can be performed across the OAE1d interval. In fact, foraminifera from both sites show good to excellent preservation, which is extremely rare for mid-Cretaceous age sediments, and of critical importance in obtaining reliable stable isotope records. For the first time we have obtained a precise record of stable isotope changes along a depth transect, providing highly resolved chemostratigraphic correlation. The data obtained from the geochemical analyses, such as a positive δ13C excursion occurring in the upper part of the R. appenninica Zone, have confirmed and improved biostratigraphic correlation between the sites. The oxygen isotope values measured on surface and deep dwelling taxa has provided a new and more detailed record of stratigraphic changes in paleotemperatures in the vertical water column and shoreward that can be correlated with a faunal turnover observed in the planktonic foraminifera assemblages in the latest Albian. The δ18O values measured from thermocline–dwelling species of Rotalipora from ...